Patterns of adherence to prescribed opioids: the differential between opioid naïve and opioid existing patients of different age groups - Zin, Che Suraya; Taufek, Nor Hidayah; Meor Ahmad, Mazlila (2019)
Background Opioid prescribing has increased tremendously in the last two decades which concomitantly increased the unwanted consequences such as opioid abuse, misuse and overdose death. Poor adherence to opioid therapy is one of the factors contributing to these problems which are associated with increased healthcare cost. Limited data are available on opioid adherence and whether different age groups play a role in adherence is unknown. Objective This study examined the adherence to opioid therapy in opioid naïve and opioid existing patients of different age groups. Methods This retrospective cohort study was conducted using pharmacy databases of tertiary hospital settings in Malaysia from 2011 to 2016. Adult patients aged ≥18 years old receiving at least two opioid prescriptions (buprenorphine, morphine, oxycodone, fentanyl, dihydrocodeine and tramadol) during the study period were included and stratified into opioid naïve and opioid existing pain patient groups. They were followed either until end of study period, discontinuation of therapy or death and were stratified into five age groups (18-40, 41-50, 51-60, 61-80 and ≥81 years old). Proportion of days covered (PDC) was used to estimate the adherence to opioid therapy which was calculated by dividing the total number of days covered with any opioids by the number of days in the follow-up period. Patients were considered adherent to opioid therapy if PDC was ≥80%. Factors associated with PDC were examined using the generalized linear modelling. The covariates used were age, sex, type of opioids and opioid daily dose. Results A total of 10569 patients with prescribing episodes of 36650 were included in the study. Of these, 91.7% (n=9696) were opioid naïve patients and 8.3% (n=873) were opioid existing patients. Adherence to opioid therapy (PDC≥80%) was achieved in 24.5% of naive patients and 19.5% of existing patients. The median therapy of PDC in naïve patients was 35.5% (IQR 10.3 -78.7) and 26.8% (IQR 8.8 -69.5) in opioid existing patients. Among different age groups, patients in older age group of ≥81 years old (28.1%) were the highest to achieve ≥80% PDC among naïve patients while patients of ages 41 to 50 years old (24.0%) were the highest in the opioid existing patients. Conclusion Adherence to opioid therapy was shown in a small group of pain patients. Opioid naïve patients were more likely to adhere to opioid therapy compared to opioid existing patients. Close monitoring is required in opioid existing patients who use opioids for long term as poor adherence may contribute to adverse events of opioids. Strategies to improve adherence are needed in these patients to improve the health outcomes.